REDISCOVER THE PAST THROUGH HERITAGE TOURISM: THE ALMOST FORGOTTEN INGGIT GARNASIH’S HOUSE - ., Rosita; ., Yunita (PEOPLE: International Journal of Social Sciences, 2015)
This paper examines heritage tourism, its history and its potentials to be a tourist attraction. Focusing on the almost forgotten part in Indonesian Independence history- The Inggit Garnish’s House- the house of Indonesian second President’s wife, this paper charts a course to enjoy the house as a tourist attraction and at the same time to have knowledge about Indonesian’s past. The house’s history is examined through literature, observation and interview, analyze its time line and interpret its representation. The house has three phase of its history, 1) before Inggit married to Soekarno, 2) when Inggit married to Soekarno, and 3) after Inggit married to Soekarno. Those three phases have its well-maintained collections that represent Indonesian women’s intelligence, domestic roles, and independent. The collections can be displayed according to those three phases in a course: 1) guest Room, displaying first phase collections that represent intelligence, 2) reading room, living room, and bed room, displaying second phase collections that represent domestic roles, and 3) powder and herbs making room, displaying third phase collections that represent independent.